Association between tea consumption and cognitive function in cognitively healthy older adults and older adults with mild cognitive impairment. Issue 4 (6th August 2021) - Xu, Hua; Fiocco, Alexandra J; Liu, Xiaohua; Wang, Tao; Li, Guanjun; Xiao, Shifu
Abstract : Background: Prospective studies suggest that tea consumption may decrease the risk for cognitive impairment in late life. However, little research has examined the association between tea consumption and cognitive performance across multiple domains. In addition, no research has examined the benefit of tea consumption on cognitive performance among older adults with existing impairment. Aims: The current study examined the association between tea consumption and performance on tasks of global cognitive function, episodic memory and executive function in cognitively healthy (CH) older adults and older adults with mild cognitive impairment (MCI). Methods: The analytical sample included 1849 community-dwelling older adults from the Shanghai Brain Aging Study (65.6% female, mean age of 69.50 (8.02) years). Following ascertainment of cognitive function, 816 were categorised as MCI. In addition to completion of a demographics questionnaire, participants reported their tea consumption and completed a battery of tests to measure global cognitive function, episodic memory and working memory. Results: Independent analyses of covariance revealed a significant association between tea consumption and measures of episodic memory; however, these associations were restricted to CH older adults but not older adults with MCI. Tea consumption was not associated with working memory performance. Conclusions: The current study suggests that the benefit of tea consumption is restricted to cognitively healthy older adults and does not extend to older adults with MCI.